'A Duel or a Date?': an Examination of queer male Eroticism in Gaetano Donizetti’s Lucia di Lammermoor (1835) and Giuseppe Verdi’s La Forza del Destino (1865) - Embourne, Oliver (2023)
Academic musicology increasingly acknowledges and uplifts the voices of queer people and their contributions to opera. In performance, many opera houses, from major players such as the Royal Opera House to small local companies are making space for queer perspectives. This includes character interpretations in productions and extra material which highlights the behind-the-scenes contributions of queer composers, directors, musical directors, and so forth. This subfield of musicology is still growing, however, which means that there is a lack of research focusing on trans and nonbinary individuals, especially transmasculine people, in opera. There is also a lack of long-form analyses of the queer subtext of individual operas, and this research aims to attempt to fill both of these gaps in the research literature. The methodology for this is to place within the existing literature a number of queer analyses of Donizetti’s Lucia di Lammermoor and Verdi’s La Forza del Destino. This is a theoretical experiment which is still rooted in the historical and musicological literature examining Donizetti and Verdi’s conceptions of masculinity, sexuality, and male-male relationships. This also includes significant focus on transmasculine experience and identity as it relates to La Forza del Destino.